2022
DOI: 10.2217/fon-2022-0589
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Certain Hematological Parameters and Risk of Breast Cancer

Abstract: Aim: To explore the association between preoperative hemoglobin-to-red cell distribution width ratio (HRR), platelet-to-monocyte ratio or monocyte-to-high-density lipoprotein ratio and risk of breast cancer. Materials & methods: The clinical data of 226 patients with breast cancer were retrospectively analyzed and compared with 199 healthy controls by multivariate logistic regression analysis. Results: Multivariate logistic regression analysis revealed that HRR (p < 0.001) and monocyte-to-high-density l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In a meta-analysis by Chi et al, a low HRR was associated with an increased risk of all-cause mortality (hazard ratio [HR] 2.29) and disease progression or relapse (HR 2.19). Additionally, the diagnostic efficacy of HRR for breast, nasopharyngeal, and lung cancers has been reported 17 , 22 , 23 . However, the diagnostic efficacy of HRR for OCs has not been reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In a meta-analysis by Chi et al, a low HRR was associated with an increased risk of all-cause mortality (hazard ratio [HR] 2.29) and disease progression or relapse (HR 2.19). Additionally, the diagnostic efficacy of HRR for breast, nasopharyngeal, and lung cancers has been reported 17 , 22 , 23 . However, the diagnostic efficacy of HRR for OCs has not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…The HRR is a prognostic marker for various malignant tumors [17][18][19][20][21]. In a meta-analysis by Chi et al, a low HRR was associated with an increased risk of all-cause mortality (hazard ratio [HR] 2.29) and disease progression or relapse (HR 2.19).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These associations were observed across all included cancer types aside from head and neck carcinoma. However, Tham et al reported that the Hb/RDW ratio was independently related to event-free survival (EFS, p = 0.017) [42,43,[72][73][74][75].…”
Section: Prognostic Value Of Hb/rdwmentioning
confidence: 99%